Деякі рецепторно-імунні характеристики ендометрію за різних форм домінування андрогенів - Семенюк, Л. М. (Clinical Endocrinology and Endocrine Surgery, 2014)
The paper studies the features of folliculogenesis, immune, morphological and functional status of the endometrium, particularly systemic immunity in women with reproductive problems, the dominance of androgens and ovulatory cycle. Found that reproductive dysfunction among women in this group are due to inhibition of folliculogenesis, the disturbance of physiological transformation of the endometrium, which is manifested overexpression of estrogen and progesterone receptors, as well as changes in the composition of NK-cells under the influence of androgen excess. Systemic manifesta-tions of androgen dominance is to reduce the number of B cells in the testosteronemiya accompablood. Insulated degidronied by a decrease amount of CD8 + T lymphocytes and an increase in the num-ber of T-helper cells in the peripheral blood, indica-ting that the sensitivity of different subpopulations of T lymphocytes to various androgens.